2017
DOI: 10.1007/978-1-4939-7459-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase I and Genome Stability: The Good and the Bad

Abstract: Topoisomerase I (Top1) resolves torsional stress that accumulates during transcription, replication and chromatin remodeling by introducing a transient single-strand break in DNA. The cleavage activity of Top1 has opposing roles, either promoting or destabilizing genome integrity depending on the context. Resolution of transcription-associated negative supercoils, for example, prevents pairing of the nascent RNA with the DNA template (R-loops) as well as DNA secondary structure formation. Reduced Top1 levels t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 140 publications
0
12
0
Order By: Relevance
“…While the low level of rU can be explained by general high concentration of dTTP in the nucleotide pools 3,23 with rUTP/dTTP being the lowest rNTP/dNTP ratio, which we observed both in S. cerevisiae and S. pombe strains ( Supplementary Fig. 1), potential activity of topoisomerase I on sequences with rU 12,39 , and some proofreading activity for Pol ε on rU 21 , its incorporation in mtDNA and nDNA of rnh201-null cells is not random. In fact, we show that rU is found in most cases after dC, and this feature is highly conserved across S. cerevisiae, S. paradoxus, and S. pombe (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…While the low level of rU can be explained by general high concentration of dTTP in the nucleotide pools 3,23 with rUTP/dTTP being the lowest rNTP/dNTP ratio, which we observed both in S. cerevisiae and S. pombe strains ( Supplementary Fig. 1), potential activity of topoisomerase I on sequences with rU 12,39 , and some proofreading activity for Pol ε on rU 21 , its incorporation in mtDNA and nDNA of rnh201-null cells is not random. In fact, we show that rU is found in most cases after dC, and this feature is highly conserved across S. cerevisiae, S. paradoxus, and S. pombe (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Until now, topoisomerase I (Top1) is the only enzyme able to cleave rNMPs embedded in DNA, when the RER pathway is not working. Top1 is an essential enzyme thought to resolve DNA supercoils generated during replication and transcription (200,201). It has been shown that Top1, cleaving at the 5′-side of rNMPs (199,202) and generating 5′-OH and 3′-cyclic 2′-3′ phosphate as DNA termini, is able to compensate for RNase H2 deficiency, although it causes high levels of DNA mutations (199,203).…”
Section: The Roles Of the Ber Pathway In Rna Processingmentioning
confidence: 99%
“…RNaseH2 is responsible for incising DNA at the 5′ side of ribonucleotides misincorporated into DNA during replication (42). In the absence of RNaseH2, topoisomearse I incises DNA at the ribose residue to give rise to PARP-trapping breaks that are highly recombinogenic (43) and that have recently been shown to sensitize RNaseH2-deficient cells to olaparib (44). As shown by pulsed-field gel electrophoresis (PFGE, Supplementary Figure S3B and C), RNaseH2A knock-down gave rise to a similar amount of DSBs as a knock-down of BRCA1, and the amount of breaks in DNA of cells in which both proteins were depleted was additive.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report demonstrated that PARPi sensitivity is augmented by the depletion of RNaseH2 (44), which removes ribonucleotides from genomic DNA (42). Ribonucleotides that remain in DNA form deleterious adducts with topoisomerase I, and processing of these adducts gives rise to DNA breaks that cause chromosomal rearrangements and that are highly-toxic to HR-deficient cells (43). There have also been attempts to combine PARPis with radiation therapy (48,49).…”
Section: Discussionmentioning
confidence: 99%